2021
DOI: 10.5860/crl.82.1.75
|View full text |Cite
|
Sign up to set email alerts
|

Student-Centered Design: Creating LibGuides Students Can Actually Use

Abstract: In this mixed-methods study, librarians at Kennesaw State University Library System conducted a year-long design research project to create a flexible subject guide “blueprint” for undergraduate students using LibGuides. Methods included a card sorting study with 18 undergraduate students and usability testing with 40 undergraduate students. The study’s goals were to identify what content, aesthetic design, organization, and structure students preferred on a subject guide. This paper addresses the current lite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 3 publications
(3 reference statements)
0
8
0
Order By: Relevance
“…2. Website Content According to the Specialty "Sports" Creating and maintaining subject guides is an ongoing challenge for many academic libraries (Barker & Hoffman, 2021). There is always the possibility that users will not wish to use the information provided in the LibGuides format.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2. Website Content According to the Specialty "Sports" Creating and maintaining subject guides is an ongoing challenge for many academic libraries (Barker & Hoffman, 2021). There is always the possibility that users will not wish to use the information provided in the LibGuides format.…”
Section: Resultsmentioning
confidence: 99%
“…The topic of the development and use of LibGuides is widely presented in the studies of foreign scientists (Mwanzu, Nakaziba, Karungi, Ayebazibwe, & Gatiti, 2022;Barker & Hoffman, 2021;Logan & Spence, 2021;Goodsett, Miles, & Nawalaniec, 2020;Paschke-Wood, Dubinsky, & Sult, 2020;Clever, 2020;Tyson & Dinneen, 2020). Abroad, LibGuides are a fairly common practice, it is a convenient format for presenting information, which significantly saves time for students, teachers, and scientists to search for the necessary scientific and educational resources.…”
Section: Introductionmentioning
confidence: 99%
“…palrap.org Barker and Hoffman (2021) noted that while librarians are often experts in subject-specific research methods, they are less knowledgeable of web design best practices (p. 75). In considering the divide between librarian expectations for research guides and student expectations for research guides, Barker and Hoffman stated that students tend to want guides that are organized around research processes, as opposed to guides organized around lists of sources related to specific subjects (pp.…”
Section: Literature Reviewmentioning
confidence: 99%
“…46 Alternatively, some have questioned the connection between the use of LibGuides and pedagogy in higher education and whether the wide adoption of the tool addresses information inequity. 47 Among academic libraries, a common theme in the literature is guide effectiveness in reaching target audiences 48 and providing library services. 49 Bowen's comparison study concluded that LibGuide and web-based tutorials are equally effective tools for delivering information literacy skills and strategies.…”
Section: Pedagogical Considerations For Libguides Ux Designmentioning
confidence: 99%